If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + 3 + -1t = 8 Reorder the terms: 3 + 5t + -1t = 8 Combine like terms: 5t + -1t = 4t 3 + 4t = 8 Solving 3 + 4t = 8 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 4t = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 4t = 8 + -3 4t = 8 + -3 Combine like terms: 8 + -3 = 5 4t = 5 Divide each side by '4'. t = 1.25 Simplifying t = 1.25
| 8-m=3m | | (6x-7)(x-9)=(x-3)(1-5x) | | Siny=0.51 | | (3x+4)(x+1)=(x+1)(2x-1) | | 5m=58 | | 3a+-22=2a | | 9=-3m+12 | | -f(x)=(3x^2)-2x-3 | | (5x-4)(x-9)=(x+16)(1-5x) | | 3x+5y+3+3x-5y= | | x-5=2-12(x+6) | | x=40x | | 30+25x=20+55x | | 2a=37 | | x+0.1x=5000 | | -32=2+-7b | | Sin(x)=.88 | | Sinx=.88 | | 24c=1440 | | ((-7a^2b^3c^0)/(3a^2b^4c^3))^-4 | | (3x-4)(x-8)=(x-6)(4x-5) | | y^2-2y-4=16y-32 | | 5n-11=3n-13 | | 5x-3-30=4x-3+6x | | (-7a^2b^3c^0)/(3a^2b^4c^3)^-4 | | 27-2x=20-8x | | 32m=2496 | | -152=-8(6x+1) | | 5x+11=5x-17 | | 4y+(-2)=34 | | 22=-3(5k+6) | | 5x+11=-8x-17 |